2009
DOI: 10.3168/jds.2008-1614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat source differing in fatty acid profile on metabolic parameters, fertilization, and embryo quality in high-producing dairy cows

Abstract: The objectives were to evaluate the effects of source of fatty acids (FA) on embryo quality of dairy cows. A total of 154 Holstein cows were assigned randomly to 1 of 2 sources of FA supplemented at 2% of the dietary dry matter as calcium salts of either palm oil (PO) or linoleic and trans-octadecenoic acids (LTFA) from 25 d prepartum to 80 d in milk (DIM). Cows were presynchronized beginning at 30 +/- 3 DIM and then subjected to the Ovsynch protocol beginning on d 39 +/- 3 postpartum. Timed artificial insemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0
28

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 28 publications
6
75
0
28
Order By: Relevance
“…Observations recorded for embryo quality at five (Cerri et al, , 2009) and seven (Thangavelu et al, 2007) days after insemination, and for embryo survival (Petit and Twagiramungu, 2006) and conception rate to first insemination (Juchem et al, , 2010 support the finding that, for the oocyte and early embryo, some fatty acids among the polyunsaturates, in particular linolenic, are superior to others.…”
Section: Introductionsupporting
confidence: 56%
“…Observations recorded for embryo quality at five (Cerri et al, , 2009) and seven (Thangavelu et al, 2007) days after insemination, and for embryo survival (Petit and Twagiramungu, 2006) and conception rate to first insemination (Juchem et al, , 2010 support the finding that, for the oocyte and early embryo, some fatty acids among the polyunsaturates, in particular linolenic, are superior to others.…”
Section: Introductionsupporting
confidence: 56%
“…Several articles have been published on the effect of nutrition on superovulation in pigs (Kojima et al, 1997) and cows (Boland et al, 2001;Fouladi-Nashta et al, 2007;Cerri et al, 2009). However, only a few studies, which have reported contradictory results, were focused on the evaluation of oocyte quality in relation to diet composition.…”
Section: Discussionmentioning
confidence: 99%
“…Há relatos de efeito dos ácidos graxos sobre: o número e o tamanho de folículos ovarianos (Lucy et al, 1991;Robinson et al, 2002;Bilby et al, 2006); o tamanho do corpo lúteo (CL) (Raes et al, 2004;Bilby et al, 2006); e a qualidade ovocitária (Kim et al, 2001;Zeron et al, 2002). Além disso, outros autores também observaram que dietas que continham ácidos graxos influenciaram a qualidade embrionária (Kojima et al, 1997;Childs et al, 2008a;Cerri et al, 2009) e a concentração circulante de prostaglandina e hormônios esteroides (Ryan et al, 1992;Petit et al, 2002;Childs et al, 2008b). Neste último caso, não estão bem definidas as causas da associação observada entre a suplementação com lipídeos e as maiores concentrações circulantes de hormônios esteroides.…”
Section: Introductionunclassified